Penerapan Algoritma Ant System dalam Menemukan Jalur Optimal pada Traveling Salesman Problem (TSP) dengan Kekangan Kondisi Jalan - Andhi Akhmad Ismail; Samiadji Herdjunanto; Priyatmadi (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2012)
The completion of Traveling Salesman Problem (TSP) is to find the shortest path to visit all of the cities. With the shortest path, it is expected that the travel time will also be shorter. In fact, when a salesman visits all of the cites in his list, he will find obstacles such as poor road conditions, congestion, damaged roads, or other constraints. Therefore, although the shortest path has been established, if there is an obstacle the travel time to all cities will be longer. One way to solve the TSP is by ant algorithm. The modifications were made to the Ant System by providing constraint pheromone to each road which could not be passed and also gave a long distance to the roads that should not be passed. The results of this study indicate that the ants never pass constrained sections, for square grid data also two data from TSPLIB95. This occurs because the segments were given constraints, the pheromone were weighted 0 and given the longest distance.